Infeksi Babesia spesies bersamaan dengan virus corona enterik kucing dan giardiasis pada dua kucing betina - Wulansari, Retno; Soesatyoratih, Roro; Widhyari, Sus Derthi; Suryono (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
The premunition stage of babesiosis poses a significant risk of relapse due to immune suppression. This report describes two cats that presented to a veterinary clinic with lethargy, anorexia of several days’ duration, watery eyes, and loose stools. Both cats were unvaccinated and lived in an open environment shared with their owners. Initial clinical evaluation suggested feline coronavirus (FCoV) infection and giardiasis; however, subsequent peripheral blood smears revealed intracellular parasites consistent with Babesia sp.. The initial treatment targeted viral and protozoal infections using antiprotozoal and antiviral agents for seven days, followed by a 21-day regimen of clindamycin and multivitamins to manage babesiosis. Hematological analysis and Giemsa-stained peripheral blood smears revealed anemia, thrombocytopenia, and persistent babesiosis. Clindamycin therapy effectively reduced parasitemia and alleviated clinical signs, including anemia, anorexia, and weakness, although complete clearance of Babesia sp. from the peripheral blood was not achieved at the administered dosage.